Coralligenous Bioconstructions Quality Index (CBQI): a synthetic indicator to assess the status of different types of coralligenous habitats. (November 2017) - Ferrigno, F.; Russo, G.F.; Sandulli, R.
Highlights: A new fast and easy index to assess the coralligenous bioconstructions quality is proposed. Different types of coralligenous habitats (cliffs, banks, and submerged shoal) are characterized and compared. Anthropic pressure, mainly represented by fishing activity, highly influences the index values. Abstract: The global interest in the assessment of quality condition of some benthic habitats on hard bottoms, such as the coralligenous bioconstruction particularly important for the biodiversity maintenance in the Mediterranean Sea, is recently increasing. Using a synthesis of recent knowledge and ROV (Remotely Operated Vehicles) imaging data acquired in the Bay of Naples (Tyrrhenian Sea, Italy), the Coralligenous Bioconstruction Quality Index (CBQI) was developed. This new index can compare different types of coralligenous habitat (rocky cliffs, submerged shoals, and platform banks) located at both shallow and deep bottoms, and calculate their quality status taking into account coralligenous communities structuring, bottom abiotic factors and anthropic stress evaluation. The data analysis was relatively fast and easy to perform due to the use of morphological groups for coralligenous characterization and anthropic impact categories mainly related to fishing activities. The CBQI may provide a useful tool for the establishment of monitoring protocols and management programs to assess the quality of coralligenous bioconstructions, in different areas of Mediterranean Sea, since it takes into account and discerns the change in communities due to environmental characteristics and/or to anthropic pressure.